3′-Phosphoadenosine 5′-Phosphate Accumulation Delays the Circadian System . Issue 4 (27th February 2018) - Litthauer, Suzanne; Chan, Kai Xun; Jones, Matthew Alan
Abstract : Accumulation of the stress-induced metabolite PAP delays the circadian system in Arabidopsis thaliana. Abstract: The circadian system optimizes cellular responses to stress, but the signaling pathways that convey the metabolic consequences of stress into this molecular timekeeping mechanism remain unclear. Redox regulation of the SAL1 phosphatase during abiotic stress initiates a signaling pathway from chloroplast to nucleus by regulating the accumulation of a metabolite, 3′-phosphoadenosine 5′-phosphate (PAP). Consequently, PAP accumulates in response to redox stress and inhibits the activity of exoribonucleases (XRNs) in the nucleus and cytosol. We demonstrated that osmotic stress induces a lengthening of circadian period and that genetically inducing the SAL1-PAP-XRN pathway in plants lacking either SAL1 or XRNs similarly delays the circadian system. Exogenous application of PAP was also sufficient to extend circadian period. Thus, SAL1-PAP-XRN signaling likely regulates circadian rhythms in response to redox stress. Our findings exemplify how two central processes in plants, molecular timekeeping and responses to abiotic stress, can be interlinked to regulate gene expression.